ANALISIS PERAN GURU DALAM PEMBELAJARAN DARING SBDP DI KELAS RENDAH SEKOLAH DASAR - Rosiana Agustina; Irna Khaleda; Luthfi Hamdani Maula (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to describe the teacher's role in online SBdP learning in class III-B SDN 1 Nagrak, Kabupaten Sukabumi. The research method used was descriptive qualitative with the type of case study. The research subjects used were class III-B teachers at SDN Nagrak. Data collection techniques used in this study were interviews, observation, and documentation. The data were analyzed by techniques proposed by Miles and Huberman, which consisted of data reduction, data display, and Conclusion/Verification. The results of the study revealed that 7 teacher roles out of 9 teacher roles were applied in the learning process. Among them were the teacher's roles as an informer, as a director, as a motivator, as a facilitator, as a mediator, as an organizer, and as an evaluator. The supporting and inhibiting factors for the teacher's role in SBdP online learning were the internal and external factors.